Nas tramas da política: uma etnografia da ação coletiva na favela de Vila Prudente - Bobadilla, Kassia Beatriz [UNIFESP] (2016)
This dissertation aims to uncover the meanings of politics and the intricacies of collective action in Favela de Vila Prudente, located on the east side of São Paulo and considered the oldest slum in the city. In this perspective, research uses an ethnographic look at the daily of slum and the actions of community leaders, organizations and other actors. Promoting a dialogue between urban anthropology and anthropology of politics, this study is part of the field of debate on urban issues and forms of organization of social groups regarded as "the margins" of the state. Following the conflicts, alliances and disputes that permeate the favela?s political relations, I pretend analyse how notions around memory and territory are articulated strategically and from different repertoires and contours that collective action acquires in this particular context and between generations of leaders and groups who work in it place